118k views
4 votes
What is the solution: –3(3x –2) = –30

User Matt Esch
by
5.4k points

2 Answers

6 votes

Answer:

X = 4

Explanation:

1: Distribute

-3 (3x - 2) = -30 (Multiply 3x and -2 by -3)

-9x + 6 = -30

2: Combine Like Terms

-9x + 6 = -30 (Subtract 6 from -30)

-9x = -36

3: Divide

-9x = -36 (Divide -36 by -9 to get x by itself)

x = -36 / -9

4: Solve

x = -36 / -9

X = 4

User NIKUNJ KOTHIYA
by
6.1k points
1 vote

Answer:

x=4

Explanation:

–3(3x –2) = –30

Divide each side by -3

–3(3x –2)/-3 = –30/-3

3x –2 = 10

Add 2 to each side

3x –2+2 = 10+2

3x = 12

Divide each side by 3

3x/3 = 12/3

x = 4

User Lee Davis
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.